Improving transparency—A call to include social housing information in biomedical research articles involving nonhuman primates - Pomerantz, Ori; Baker, Kate C.; Bellanca, Rita U.; Bloomsmith, Mollie A.; Coleman, Kristine; Hutchinson, Eric K.; Pierre, Peter J.; Weed, James L. (American journal of primatology, 2022)
The social setting of animal subjects in the research environment has known effects on a variety of dependent measures used in biomedical research. Proper evaluation of the robustness of published research is dependent upon transparent, detailed, and accurate reporting of research methods, including the animals' social housing conditions. However, to date, most research articles utilizing nonhuman primates (NHPs) provide only partial data on this topic, hampering transparency, and reproducibility. Therefore, we call for the inclusion of information pertaining to the social aspects of the animals' housing conditions in publications involving NHPs to improve transparency. We argue that including this information in scientific publications is crucial for the interpretation of research findings in the appropriate context and for understanding unexplained variability in study findings. Finally, the inclusion of this information in publications will additionally familiarize scientists with how other researchers conducting similar studies are housing their animals and will encourage them to consider the implications of various housing conditions on their research outcomes Highlights Transparency of study findings is a key principle of the scientific method. Enabling transparency requires detailed and accurate reporting of all study‐related elements. Social aspects of the housing of nonhuman primates (NHPs) in research are known to influence biological functioning. Incorporating a requirement to include specific information pertaining to the social aspects of NHP housing will increase transparency.